Correction: Constant-potential environment for activating and synchronizing cardiomyocyte colonies with on-chip ion-depleting perm-selective membranes. Issue 18 (1st September 2021) - Yadav, Vivek; Chong, Nicolas; Ellis, Bradley; Ren, Xiang; Senapati, Satyajyoti; Chang, Hsueh-Chia; Zorlutuna, Pinar
Abstract : Correction for 'Constant-potential environment for activating and synchronizing cardiomyocyte colonies with on-chip ion-depleting perm-selective membranes' by Vivek Yadav et al., Lab Chip, 2020, 20, 4273–4284, DOI: ; 10.1039/D0LC00809E .